Atypical Presentation of Sengers Syndrome: A Novel Mutation Revealed with Postmortem Genetic Testing. (3rd March 2020) - Guleray, Naz; Kosukcu, Can; Taskiran, Zihni Ekim; Simsek Kiper, Pelin Ozlem; Utine, Gulen Eda; Gucer, Safak; Tokatli, Aysegul; Boduroglu, Koray; Alikasifoglu, Mehmet
Abstract: Introduction: Sengers syndrome is an autosomal recessive disorder characterized by congenital cataracts, hypertrophic cardiomyopathy, skeletal myopathy and lactic acidosis. The causative AGK mutations have been identified with whole exome sequencing. Clinical report: We report on a 9-month-old infant with episodic lactic acidosis who died before a definitive diagnosis could be established. Postmortem genomic autopsy revealed a novel homozygous NM_018238: c.1215dupG; p.Phe406Valfs*4 mutation in AGK (OMIM 610345) confirming the diagnosis of Sengers syndrome. Conclusion: This report provides further evidence that reverse genetics is a useful approach in patients who do not manifest the hallmark features of known and recognizable syndromes.